2011
DOI: 10.2174/1874357901105010136
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Alternanthera mosaic virus and its Coat Protein

Abstract: A new isolate of Alternanthera mosaic virus (AltMV-MU) was purified from Portulaca grandiflora plants. It has been shown that the AltMV-MU coat protein (CP) can be efficiently reassembled in vitro under different conditions into helical RNA-free virus-like particles (VLPs) antigenically related to native virus. The AltMV-MU and VLPs were examined by atomic force and transmission electron microscopies. The encapsidated AltMV-MU RNA is nontranslatable in vitro. However, it can be translationally activated by CP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
26
0
4

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(33 citation statements)
references
References 15 publications
3
26
0
4
Order By: Relevance
“…Ранее в нашей лаборатории было показано, что БО ВМАльт способен к образованию протя-женных вирусоподобных частиц в отсутствии РНК в различных условиях [7]. Такая полимеризация БО ВМАльт затрудняет анализ формирования вРНП при инкубации БО ВМАльт с 5′-концевыми транскриптами РНК ВМАльт.…”
Section: результаты и обсуждениеunclassified
See 1 more Smart Citation
“…Ранее в нашей лаборатории было показано, что БО ВМАльт способен к образованию протя-женных вирусоподобных частиц в отсутствии РНК в различных условиях [7]. Такая полимеризация БО ВМАльт затрудняет анализ формирования вРНП при инкубации БО ВМАльт с 5′-концевыми транскриптами РНК ВМАльт.…”
Section: результаты и обсуждениеunclassified
“…Данные по подавле-нию трансляции РНК в составе вРНП свидетель-ствуют о том, что в случае ВМАльт участок инициа-ции сборки также находится на 5′-конце молекулы РНК [6,7].…”
unclassified
“…Èñ-ñëåäîâàíèå ïðåïàðàòîâ âèðóñîïîäîáíûõ ÷àñòèö ìå-òîäîì ïðîñâå÷èâàþùåé ýëåêòðîííîé ìèêðîñêîïèè ïðîâîäèëè, êàê îïèñàíî â ðàáîòå [6].…”
Section: ìàòåðèàëû è ìåòîäûunclassified
“…1, À). Áûëî ïîêàçàíî, ÷òî âûäåëåííûé èç ïðå-ïàðàòà AltMV-MU ÁÎ ñïîñîáåí îáðàçîâûâàòü ÂÏ× in vitro â îòñóòñòâèå âèðóñíîé ÐÍÊ [6].…”
Section: ðåçóëüòàòû è îáñóAeäåíèåunclassified
“…According to Lough et al [14], regulatory elements required for PVX reconstitution span the 5 0 -proximal 1-107-nt fragment of PVX RNA. It has been reported that the papaya mosaic potexvirus [16] and alternanthera mosaic potexvirus [17] assembly were also initiated at the 5 0 end of its RNA. 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 Previously, we have shown that in vitro incubation of PVX CP with heterologous RNAs of a number of plant and animal viruses belonging to various taxonomic groups produced viral ribonucleoproteins (vRNPs) whose morphological and translational properties were identical to those of cognate reassembled vRNP (PVX RNAePVX CP).…”
Section: Introductionmentioning
confidence: 99%